Impact of working capital on the profitability of South African firms listed on the Johannesburg Stock Exchange - Ncube, Mkhululi (My University, 2013)
This study examines the influence of working capital management components on the profitability of South African firms listed on the Johannesburg Stock Exchange (“JSE”). In addition, the study investigates how the influence of the selected working capital management components changes as macroeconomic conditions change. The study used accounting based secondary data obtained from I-Net Bridge and BF McGregor for 254 firms from 2004 to 2010. The Pooled Ordinary Least Squares (“OLS”) regression models were used in the analyses. The key findings from the study indicate the following: (1) that there exists a significant negative relationship between the net time interval between actual cash expenditures on a firm‟s purchase of productive resources and the ultimate recovery of cash receipts from product sales (cash conversion cycle) and profitability. This negative relationship suggests that managers can create value for the shareholders of the firm by reducing the cash conversion cycle; (2) that there exists a significant negative relationship between days sales in receivables and profitability. This indicates that slow collection of accounts receivables is associated with low profitability and suggests that corporate managers can improve profitability by reducing credit period granted to their customers; (3) that an increase in the length of a firm‟s cash (operating) cycle tends to increase profitability during an economic recession than during an economic boom. This result indicates that firms adopt a more generous trade credit policy during an economic recession than during a boom in an attempt to boost sales which would ordinarily dwindle during a recession. The implication of this positive relationship in comparison with a negative relationship between the normal cash conversion cycle and profitability is that corporate managers need to streamline their trade credit policy and change it accordingly as the macroeconomic environment changes in ensuring that the company‟s sales are not adversely impacted as economic conditions change. Furthermore, the study finds that there exists a highly significant negative relationship between profitability and the following respective ratios: days payables outstanding, current ratio, and capital structure. The negative relationship found between profitability and debt to equity ratio (used as a proxy for capital structure) indicates that South African firms‟ profitability tends to decrease at excessively high and increasing levels of debt.
Keywords: Financial management; Capital structure; Corporations; South Africa